The effect of job satisfaction and job stress on employee performance CV.Synergy - Stivaniyanti Atmanegara; Habibullah Arief; Emha Diambang Ramadhany; Aurelia Reyza Safitri Husaini; Rieke Fenita Lorenza; Mahendra, I Dewa Made Yuda (Jurnal Ekonomi, 2024)
The aim of this research is to evaluate the impact of job satisfaction and work stress on employee performance at CV.Sinergi, both separately and simultaneously. This research uses an explanatory approach, with a population involving all employees at CV.Sinergi, namely 40 people, with a research sample of 35 people. The type of data collected consisted of primary and secondary data, using questionnaires and interviews as data collection instruments. To ensure data quality, validity and reliability tests were carried out. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that partially, both job satisfaction and job stress have an influence on employee performance. Simultaneously, job satisfaction and work stress influence employee performance at CV.Sinergi